Service Learning based on ESD and Sustainability Awareness Profile of Students in Bandung - Nurhaliza; Rustaman, Nuryani (IJER (Indonesian Journal of Educational Research), 2023)
This study aims to measure the level of students’ service to the community related to sustainability, and to measure the level of students’ awareness of sustainability values. The method used in this research is a case study. The instruments used in this study consisted of ESD-based service learning questionnaires, sustainability awareness profile questionnaires and interviews. Instruments were given to 37 students of one of senior high schools in Bandung. The sampling technique used is a purposive sampling technique. The consideration of choosing the samples is based on suggestions from the teacher of the subjects concerned. The results showed that ESD-based service learning as a whole obtained an average of 76.9%, meaning that it has been applied well even though it has not been done continuously, but is in the habituation stage. Then, in terms of Sustainability Awareness Profile, students are included in the medium criterion. The results of the student's Sustainability Awareness Profile are divided into 3 categories, namely sustainability practice awareness with a percentage of 73.74% is always carried out, behavioral and attitude awareness a percentage of 87.06% is always carried out, and emotional awarenss with a percentage of 66.26% is being carried out. So that students' sustainability awareness attitude can support the concept of continuing education or ESD even with the results of the Sustainability Awareness Profile in the medium category.